On the use of multilevel modeling as an alternative to items analysis in psycholinguistic research - Locker, Jr, Lawrence; Hoffman, Lesa; Bovaird, James A (Behavior research methods, 2007)
The use of multilevel modeling is presented as an alternative to separate item and subject ANOVAs (F1 x F2) in psycholinguistic research. Multilevel modeling is commonly utilized to model variability arising from the nesting of lower level observations within higher level units (e.g., students within schools, repeated measures within individuals). However, multilevel models can also be used when two random factors are crossed at the same level, rather than nested. The current work illustrates the use of the multilevel model for crossed random effects within the context of a psycholinguistic experimental study, in which both subjects and items are modeled as random effects within the same analysis, thus avoiding some of the problems plaguing current approaches.